PCR-based differentiation of Fasciola species (Trematoda: Fasciolidae), using primers based on RAPD-derived sequences. - McGarry, J.W. (2007)
The zoonotic liver flukes Fasciola hepatica and F. gigantica co-exist in parts of Africa and Asia. The two species have similar life-cycles but different transmission characteristics. Although the identification of adult Fasciola to species level is traditionally based on differences in size and shape, recent studies have demonstrated this method to be unreliable. Species of Fasciola can be distinguished by staining and comparing the morpho-anatomy of the gut and ovaries or by iso-enzyme analysis but such approaches are time-consuming and require specialist skills. Two primer sets, based on RAPD-derived sequences from English F. hepatica and Ghanaian F. gigantica, can now be used, in two separate PCR, to distinguish F. hepatica from F. gigantica. When the PCR were used to investigate 10 flukes (five from the U.K. and five from Peru) morpho-anatomically identified as F. hepatica and 10 (five from Ghana and five from Sudan) morpho-anatomically identified as F. gigantica, all 20 flukes were correctly identified to species level. The PCR were validated using 175 flukes collected, over a 12-year period, from different countries and both cattle and sheep.